1972
DOI: 10.1128/aem.23.3.637-648.1972
|View full text |Cite
|
Sign up to set email alerts
|

Microflora of Soil as Viewed by Transmission Electron Microscopy1

Abstract: Several procedures were evaluated for separating and concentrating indigenous microorganisms from soil without the occurrence of growth. Electron microscopy of nontangential, thin sections through these cells revealed that all of the cells examined were less than 0.9 gm in diameter, and up to 72% were "dwarf' cells less than 0.3 gim in diameter. Some were small enough that they should not be resolved with the light microscope. Approximately 27% had a fine structure bearing some resemblance to that of a bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…trifolii are small enough to pass through 0.4plm-pore-size filters (2). This observation supports various reports stating that there is a high proportion of bacterial cells in soil that are atypically small relative to those grown on laboratory media (3,4,6,8,13,26) and that only a small fraction of this small-cell population can be cultured (7).…”
supporting
confidence: 91%
“…trifolii are small enough to pass through 0.4plm-pore-size filters (2). This observation supports various reports stating that there is a high proportion of bacterial cells in soil that are atypically small relative to those grown on laboratory media (3,4,6,8,13,26) and that only a small fraction of this small-cell population can be cultured (7).…”
supporting
confidence: 91%
“…As reported previously, thin-tical. This not only increases the ease of thinsectioning requires that all gritty soil debris be sectioning but also improves cell recognition in removed from the sample (1,2). In those studies, replicas of frozen-etched preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The resident microorganisms in soil can be released from the soil debris and concentrated so that they can be viewed by transmission electron microscopy as thin sections (1,2) or replicas of frozen-etched preparations (3). For thin-sectioning (1,2),most ofthe gritty soil debriswas removed by an exhaustive centrifugal washing procedure, but the freeze-etching technique (3) used only a 'Received July 4,1974. 'This research was authorized for publication as paper No.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of soil bacteria are known to be less than 0.5 m in diameter (6,7,8,17,27), and it has been suggested that this population of small bacteria consists mainly of gram-positive organisms (32). These bacteria do not grow well under laboratory conditions (7), and their growth rate, as determined by the thymidine technique, may be lower than the growth rate of larger bacteria (4).…”
mentioning
confidence: 99%